Financial Management Strategies of Small Eateries in Competitive Markets: A Qualitative Study - Laia, Damai Sehati; Widagdo, C. Susmono (International Journal of Integrative Sciences, 2024)
This study aims to explore the financial management strategies employed by small eatery owners to sustain operations and remain competitive in local markets. Using a qualitative approach, data were collected through in-depth interviews with small eatery owners to uncover their practices in cash flow management, operational cost control, working capital optimization, and the adoption of financial technology. The findings reveal that: (1) Daily Cash Flow Management is a fundamental practice where owners manually record income and expenses, enabling them to monitor cash flow and allocate resources efficiently. (2) Operational Cost Control is prioritized by minimizing food waste, negotiating with suppliers for better prices, and relying on family members for labor to reduce costs. (3) Efficient Use of Working Capital is achieved by allocating resources to essential materials, while some owners resort to informal loans for urgent needs, ensuring liquidity without accumulating debt. (4) Adoption of Simple Technology for Financial Record-Keeping is emerging, with some owners using mobile apps to track finances, although barriers such as lack of knowledge and resistance to change hinder widespread adoption. The study highlights the need for targeted interventions, such as financial education and accessible technological solutions, to support small eatery owners. Future research should focus on the impact of formal financial training and broader technology adoption on the long-term success of small eateries